2017
DOI: 10.1088/1361-6579/aa6ec6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnea: a review of diagnostic sensors, algorithms, and therapies

Abstract: This review provides a current perspective of the classes of tools at hand, along with a sense of their relative strengths and areas for further improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 216 publications
0
19
0
2
Order By: Relevance
“…Continuous positive airway pressure (CPAP) is the gold standard treatment for OSA [22,23], which consists of a mechanical device that prevents upper airway collapse during sleep. Numerous studies have shown that CPAP is an effective treatment in improving OSA primary outcomes such as the number of episodes of apnoea and hypopnoea per hour of sleep (i.e., apnoea-hypopnoea index, AHI) and excessive daytime sleepiness, reducing therefore the majority of symptoms and consequences of this condition [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) is the gold standard treatment for OSA [22,23], which consists of a mechanical device that prevents upper airway collapse during sleep. Numerous studies have shown that CPAP is an effective treatment in improving OSA primary outcomes such as the number of episodes of apnoea and hypopnoea per hour of sleep (i.e., apnoea-hypopnoea index, AHI) and excessive daytime sleepiness, reducing therefore the majority of symptoms and consequences of this condition [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we focus on the usefulness of blood oxygen saturation (SpO 2 ) and airflow, which are commonly involved in type IV devices. Individually, both signals have been found to provide relevant information for OSA diagnosis [9][10][11][12] . Notwithstanding, the potential complementarity of the features derived from both signals has been marginally studied 13 .…”
mentioning
confidence: 99%
“…For serial transmission baud rate is taken as 9600 bps and sampling rate of 320 samples per second is used. Arduino Uno has a built in USART communication feature which allow USART transmission and reception via digital pins 1 and 0 [15]. For serial communication pin 1 and pin 0 of Arduino UNO needs to connect with Bluetooth modules Rx and Tx.…”
Section: Arduino Unomentioning
confidence: 99%